Family caregivers' perspectives on communication with cancer care providers. Issue 6 (2nd November 2019) - Washington, Karla T.; Craig, Kevin W.; Parker Oliver, Debra; Ruggeri, Jeffrey S.; Brunk, Samantha R.; Goldstein, Andrea K.; Demiris, George
Abstract: Purpose/Objectives: Family caregivers of individuals living with cancer are often highly involved in communication with healthcare teams, yet little is known about their experiences, needs, and preferences in this role. To address this gap in the knowledge base, researchers sought to explore family caregivers' perspectives on communication with oncology care providers. Design and Methods: Researchers conducted a secondary inductive thematic analysis of qualitative interviews originally collected as part of a randomized clinical trial of a supportive intervention for family caregivers of patients with cancer ( N  = 63). Participants: Participants were family caregivers of adult patients with cancer. Most were patients' spouses/long-term partners (52.3%) or adult children/grandchildren (29.2%). Caregivers of patients with all cancer types and stages of disease progression were eligible for study enrollment. Findings: Caregivers valued communication with healthcare providers who were attentive, genuine, broadly focused on patients and caregivers' experiences, sensitive to unmet information needs, and responsive to the potentially different communication preferences of patients and caregivers. Interpretation: Family caregivers expressed a strong preference for person-centered communication, conceptualized as communication that helps healthcare providers meet the needs of patients and caregivers both as individuals and as an interdependent unit of care, and that acknowledges individuals' experiences beyond their prescribed roles of "cancer patient" and "caregiver." Implications for Psychosocial Oncology Practice: Psychosocial oncology providers' strong orientation to the biopsychosocial and spiritual aspects of cancer care delivery make them uniquely positioned to support family caregivers. Findings suggest that providers should explicitly communicate their commitment to both patient and family care, involve family caregivers in psychosocial assessment activities and subsequent intervention, and strive to honor patients and caregivers' potentially different communication preferences.